2010
DOI: 10.1007/s11845-010-0667-z
|View full text |Cite
|
Sign up to set email alerts
|

A study of needle stick injuries among non-consultant hospital doctors in Ireland

Abstract: A needle stick injury (NI) history is greater among surgical NCHDs than medical NCHDs. The level of disposable glove usage is worryingly poor. Training in sharps handling and dealing with a NI needs to be addressed. HIV is the blood-borne infection most fear of being contracting as a consequence of a NI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…In the current study, 92.5% of HCWs knew that HBV, HCV, and HIV could be transmitted by NSIs, which is consistent with the findings of a Malaysian study (43) but higher than those reported in Bosnia (45) and Delhi (33). In this study, only 65.8% knew that this risk of Hepatitis B transmission is higher than the risk of HIV, which is less than that observed (82%) in the Irish study (46).…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, 92.5% of HCWs knew that HBV, HCV, and HIV could be transmitted by NSIs, which is consistent with the findings of a Malaysian study (43) but higher than those reported in Bosnia (45) and Delhi (33). In this study, only 65.8% knew that this risk of Hepatitis B transmission is higher than the risk of HIV, which is less than that observed (82%) in the Irish study (46).…”
Section: Discussionsupporting
confidence: 86%
“…Although a majority of respondents subjectively reported a positive knowledge level for treating a needlestick injury appropriately, only a minority showed sufficient knowledge related to occupational safety about post-exposure prophylaxis of hepatitis B- and C-virus infection and HIV. Other studies in this field also revealed deficits regarding the respective aftercare [37,56,57], finding the same gap between subjective statements and tested knowledge. Interestingly, more respondents reported the sufficient competency of appropriate behaviour in the case of needlestick injuries.…”
Section: Discussionsupporting
confidence: 56%
“…We read with great interest the recent publication by O'Sullivan et al [1] in addition to our research group's recent publication [2], also on needlestick injuries (NIs) among non-consultant hospital doctors (NCHDs) in Ireland. As readers can clearly see from these publications NIs are a major concern among healthcare professionals in Ireland, throughout their working life.…”
Section: Dear Editormentioning
confidence: 99%